A STUDY ON THE ATTITUDES OF STUDENTS TAKING ACCOUNTING COURSES IN HEALTH DEPARTMENTS TOWARDS ACCOUNTING (Third Sector Social Economic Review, 2025)
This research aims to investigate the attitudes of the students studying in health departments and taking accounting courses towards accounting. A questionnaire was chosen as the data collection method in the study. Sakarya University of Applied Sciences, Akyazı Health Campus, 183 students who have taken and are taking accounting courses (Health Management Undergraduate Degree - 120 Persons, Health Institutions Management - 120 Persons, Health Tourism Management - 120 Persons) from 360 student population, were reached by sampling 183 students who follow active courses. A questionnaire was applied to determine their attitudes towards Since accounting courses are generally perceived as difficult by students, their attitudes towards accounting are negative. However, the importance of the course in business life and the necessity of training is seen as a motivating factor in terms of accounting education. Accounting, which has an important function in health businesses, needs to act with a new perspective on sustainability and strategically in the new normal. It has been determined that there are significant differences in the accounting lesson according to the gender of the students in the health departments and that the males perform more positive-positive actions in their attitudes towards the accounting lesson.
Keywords: Healthcare Businesses; Accounting; Quantitative Research; Attitude.